Characterization of Electrical Quantities of a Grape Dye-Sensitized Solar Cell. Issue 1 (November 2020) - See, S C; Mercado, M M; Corpuz, J Z; Balbin, J; Chua, E
Abstract: A significant solution to the current global energy demand worldwide is the advancement of renewable energy, and one of these major renewable resources is the conversion of solar energy to electricity that is made possible by solar cells. In this study, the electrical quantities of a dye-sensitized solar cell were characterized to determine its efficiency, which is usually the main basis for this prototype. The researchers used a grape dye-sensitized solar cell composed of conductive glass as the photo-electrode, titanium dioxide (TiO2) sensitized with grape anthocyanin ethanol-based dye, KI3 electrolyte, and conductive glass with carbon as the counter-electrode. In characterizing the electrical quantities, the room temperature, lux level, and cell size were held constant at 23°C, 1500 lux, and 2.032cm x 1.524cm as controlled testing parameters. The researchers determined the voltage (Voc) and current (Isc) by using open and short circuit tests. The measured values were: 0.43 V; 0.40 V; 0.40 V; 0.45 V; 0.41 V and 41 µA; 38 µA; 35µA; 41µA; 39µA respectively. The computed efficiency of the cells were 1.22%, 1.05%, 0.94%, 1.29%, and 1.11% respectively.